Impact of Maternal Risk Factors on Birth Weight of Newborn in Two Maternity Hospitals in Baghdad City - jeid, Shukria; Abbas, ikbal (Iraqi National Journal of Nursing Specialties, 2006)
Objectives: A cross sectional analytic study was carried out to identify the maternal risk factors whichcontribute to occurrence of low birth weight, and to determine the statistical significant differences between lowbirth weight and maternal risk factors.Methodology: A purposive sample of (400) woman was selected from AL-Elwyia Maternity Teaching Hospitaland Fatima Al-Zaharia Maternity and Pediatric Teaching Hospital. Data was collected through the interview ofmothers. Questionnaire format was designed and consisted seven parts, demographic variables, and reproductivevariables , Reproductive health variables, complications during the current pregnancy, the mother newbornvariables nutritional status for the mother , antenatal care services, and the psychosocial status for pregnantwomen. Validity and reliability of the questionnaire were determined by conducting a pilot study. Descriptiveand inferential statistical procedures were used to analyze the data.Results: The results of the study revealed that the most of them their age was ranged between (20-34) years, andthe highest percentage of them were graduated of primary school and less, most of them were housewiveswith low socioeconomic status. The result indicated that there were five important variables contributed to theincidence of low birth weight and these variables were gestational age nutrition status, previous low birthweight, and psychosocial status for pregnant women during pregnancy and the age of mothers.Recommendations: it is recommended to emphasize on prenatal care as early as possible and improve healthservices rendered to mothers during pregnancy that the nurse must take the role in reducing the incidence ofLBW.